Nonsimilar convective thermal transport analysis of EMHD stagnation Casson nanofluid flow subjected to particle shape factor and thermal radiations - Hussain, Muzamil (International communications in heat and mass transfer)
Nanofluids are quite popular among researchers due to their high heat transfer rates, which have significant industrial applications. The primary objective of this article is to give a novel analysis of the two-dimensional electromagnetohydrodynamic (EMHD) stagnation point flow of Casson nanofluid with heat source/sink and thermal radiations. Nanoparticles such as Iron Oxide (Fe2O3) and Gold (Au)) are used with blood as base fluid. Nanomaterials are classified into several categories based on their shapes, properties, and sizes. The effects of shape factors namely sphere, tetrahedron, hexahedron, column, and lamina with various parameters are also included in this analysis. This study presents the implementation of single-phase (Tiwari-Das) model for Casson nanofluid by considering blood as base fluid. Instead of the Buongiorno model, which largely depends on Brownian and thermophoresis diffusion effects for heat transfer analysis. The single-phase model incorporates the volume fraction of nanoparticles for the evaluation of heat transfer. Relying on the Tiwari-Das model for nanofluids, a mathematical framework is constructed. To simplify the governing flow equations, proper nonsimilar conversions are used to appropriately transform the given partial differential system to dimensionless form. The rehabilitated mathematical model is simulated by employing local non-similarity technique via bvp4c. The consequences of sundry parameters against velocity and temperature profiles of Casson nanofluid are presented pictorially. The velocity profile is observed to decrease with increasing Casson fluid parameter values while enhancement is noticed with rising electric field parameter values. The temperature profile improves with increasing magnetic number, nanoparticle concentration, Eckert number, Biot number, and heat generation parameter, whereas it degrades with increasing electric field parameter. Temperature profile is maximum for lamina shaped particle while it has minimum values for sphere shape nanoparticles. The Nusselt number and skin-friction coefficients are also introduced as tools for determining the physical characteristics of Casson nanofluid flow. The obtained results of this model meticulously match those existents in the literature for various limiting constraints. The authors discussed the local non-similarity technique for simulating the dimensionless non-similar structure. To the best of authors observations, no such study for the considered flow model is yet published in literature.